2022
DOI: 10.3390/ijerph192013075
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Monetary Incentives on Physicians’ Effort and Patient Satisfaction: Understanding the Links between Monetary Incentives and Physicians’ Effort

Abstract: How monetary incentives promote physicians’ job performance in terms of patient satisfaction has been widely discussed. The incentive dilemma debate concerns whether monetary incentives reduce physicians’ intrinsic motivation at work and even lead to moral hazard. This study investigated monetary incentive policies in a hospital and analyzed how monetary incentives affect performance and behavior. By means of income composition grouping, a treatment group and control group were established, and the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…En uno de los estudios consultados, Yu et al, (2022) exponen cómo los incentivos monetarios promueven el desempeño laboral debatiendo si estos últimos reducen la motivación intrínseca que puedan conducir a un riesgo moral. Los resultados empíricos de la investigación mostraron que, aunque no se introdujeran medidas con relación a los incentivos monetarios, el objeto de estudio mejoraría de forma proactiva por la experiencia y con ello permitiendo que el empleado se sintiera motivado por su trabajo.…”
Section: Resultsunclassified
“…En uno de los estudios consultados, Yu et al, (2022) exponen cómo los incentivos monetarios promueven el desempeño laboral debatiendo si estos últimos reducen la motivación intrínseca que puedan conducir a un riesgo moral. Los resultados empíricos de la investigación mostraron que, aunque no se introdujeran medidas con relación a los incentivos monetarios, el objeto de estudio mejoraría de forma proactiva por la experiencia y con ello permitiendo que el empleado se sintiera motivado por su trabajo.…”
Section: Resultsunclassified
“…To solve this, in the short term, the savings of expenses from PCC can be used to expand welfare and job resources for physicians. This can be done through incentive plans that reward physicians for promoting communication and hard work ( 53 ). Moreover, in the long term, forming a patient-centered organizational culture ( 54 ) and providing psychological safety and perceived organizational support ( 55 ) can also be effective methods to promote PCC in practice.…”
Section: Discussionmentioning
confidence: 99%
“…22,47 It was found that nearly 70% of the PCPs regarded income as the most important motivating factor, which was consistent with previous study. 44,45 The absolute income level of the PCPs is generally low especially compared with the income level of other health sectors and professionals, 46,47 so earning more monetary income still being their dominant need. In addition, it is also found that the PCPs who regarded income as the most important motivating factor had lower scores on all three dimensions of job performance, which implies that income not satisfying the need of PCPs had direct destructive effect on their work performance.…”
Section: Discussionmentioning
confidence: 99%